The Function of Paraventricular Thalamic Circuitry in Adaptive Control of Feeding Behavior - Petrovich, Gorica D. (Frontiers in Behavioral Neuroscience, 2021)
The paraventricular nucleus of the thalamus (PVT) is a complex area that is uniquely embedded across the core feeding, reward, arousal, and stress circuits. The PVT role in the control of feeding behavior is discussed here within a framework of adaptive behavioral guidance based on the body’s energy state and competing drives. The survival of an organism depends on bodily energy resources and promotion of feeding over other behaviors is adaptive except when in danger or sated. The PVT is structurally set up to respond to homeostatic and hedonic needs to feed, and to integrate those signals with physiological and environmental stress, as well as anticipatory needs and other cognitive inputs. It can regulate both food foraging (seeking) and consumption and may balance their expression. The PVT is proposed to accomplish these functions through a network of connections with the brainstem, hypothalamic, striatal, and cortical areas. The connectivity of the PVT further indicates that it could broadcast the information about energy use/gain and behavioral choice to impact cognitive processes—learning, memory, and decision-making—through connections with the medial and lateral prefrontal cortical areas, the hippocampal formation, and the amygdala. The PVT is structurally complex and recent evidence for specific PVT pathways in different aspects of feeding behavior will be discussed.